Plan estratégico de marketing para la piladora de arroz el gallo del cantón Macará provincia de Loja - Ludeña Ramírez, Franz Artidoro (2014)
The investigation about the topic: “PLAN DE MARKETING PARA LA PILADORA DE ARROZ EL GALLO DEL CANTÓN MACARÁ PROVINCIA DE LOJA”, was developed in Macará city, having as general objective: To elaborate a strategic Plan of Marketing, with the purpose of improving the economic and productive development of the company, since the strategic plan of marketing is an essential instrument in any company or organization, because it facilitates an effective commercialization to us of any kind of product or service. In drafting the final report of the investigation, is satisfied with the dispose of art. 151 of the Academic Regime Regulation of Loja’s National University, which is entitled in the following order. Literal a. - Title. - Which corresponds to the topic of the investigation. " Literal b.- Summary.- is a summing up of the relevant parts of the investigation. Literal c.- Introduction.- highlights the importance about the researched topic Which there will be had a global Knowledge of the completed work. Literal d.- Literature Review.- Consisting of citations that contains theoretical contexts about the strategic marketing plan such as: concepts and importance of the most commonly topics used in the present work. Literal e.- Materials and methods.- where the emphasis is on explaining the methods used in the research such as deductive, inductive and descriptive analytical method, techniques such as direct observation, interviews, surveys and procedures used in the research, which allowed to collect the necessary information, as well as identify the main internal and external problems that affecting the company. Literal f.- Results.- In which the historical overview of the company is detailed. Then a FODA analysis is made, in which internal factors were determined such as: the strengths and weaknesses and the external factors that are the opportunities and threats, then the high-impact matrix criteria and assessment is performed with its respective percentages. Literal g.- Discussion- in which there was elaborated an strategic marketing plan to improve the business activity of the “PILADORA DE ARROZ EL GALLO”. Literal h.- More important conclusions of the investigation Literal i.- Recommendations -. The most important situations obtained during the application of analysis of all the researched work are described in order to the manager takes the necessary corrective policies in benefit of his company. Literal j.- Bibliography, where are announced the sources of information used for the development of the present work Literal k.- Annexes.- where is the project of investigation, as well as the model of the surveys made to the workers as to his clients and photos of the company